A Novel MPPT Scheme for an Unequally Irradiated Solar Photovoltaic Panels Feeding a Common Load Using Sliding Mode Controller - Vennila, C.; Vijayaraj, M. (Current Signal Transduction Therapy, 2018)
In this work the maximum power point tracking of solar photovoltaic panels that are operating in the same area for a common load but subjected to an unequal solar insolation levels. It is proposed that a separate DC to DC converter is used for each of the panels. Sliding mode controller is adopted for the MPPT. The MATLAB SIMULINK simulation and the experimental verification validates that the proposed idea harvests more power than the common optimised duty cycle that is used in a single power converter. Methods: In the existing scheme where a number of panel are operating in parallel a common DC to DC converter is used. For the purpose of MPPT and optimisation technique is used to arrive at the duty cycle to be adopted in the common DC to DC converter. Such a method guarantees the overall maximum possible power output for that particular method using a single DC to DC converter with a single duty cycle. It does not guarantee the maximisation of the power output of the individual solar PV panels which is the actual maximum power harvestable for the given environmental condition. In the proposed technique, applicable to solar trees where a number of panels are physically arranged in different angles so as to harvest maximum power all through the day, it is more effective to use individual dc to dc converters with individual duty cycles. In this work the sliding mode control based on the PV terminal voltage is adopted. Results: The proposed idea is simple, no rigorous mathematical implications, requires less number of sensors, and requires no explicitly PWM circuits. It can be used readily in real life applications.
Keywords: Solar photovoltaic tree